2018
DOI: 10.1016/j.compstruct.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the mechanical behaviour of 3D carbon/carbon composites under biaxial compression

Abstract: The effects of complex state of stress on the compressive behaviour of 3D carbon/carbon composites are investigated by application of uniaxial and biaxial loadings using a specially developed Zwick cruciform testing facility. The shape of the biaxially loaded cruciform specimen is optimised to avoid premature fracture outside the gauge section. A semi-analytical method is proposed to determine the stress components in the gauge section of the biaxial specimen. The experimentally obtained failure stress relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As a summary, the equipment with the best acceptance in the scientific community follows this same scheme of two orthogonal pairs of axially aligned actuators with independent load cells, whether they are electromechanical or hydraulic. Examples of similar facilities are found in [16,17,[41][42][43][44][45][46][47]. Hannon and Tiernan [48] reviewed the in-plane biaxial systems applied to the characterisation of sheet metal because biaxial states can be present in sheet metal forming processes and the interest of the biaxial response due to the anisotropy resulting in the material after manufacturing.…”
Section: Load Framementioning
confidence: 99%
See 2 more Smart Citations
“…As a summary, the equipment with the best acceptance in the scientific community follows this same scheme of two orthogonal pairs of axially aligned actuators with independent load cells, whether they are electromechanical or hydraulic. Examples of similar facilities are found in [16,17,[41][42][43][44][45][46][47]. Hannon and Tiernan [48] reviewed the in-plane biaxial systems applied to the characterisation of sheet metal because biaxial states can be present in sheet metal forming processes and the interest of the biaxial response due to the anisotropy resulting in the material after manufacturing.…”
Section: Load Framementioning
confidence: 99%
“…Another noteworthy advantage of the strain gauge technology is the need of a small space for its placement and wiring, which makes it an ideal technique for tests in which access to the specimen is limited [58,74,82]. An application that demonstrates the versatility of strain gauges is the ability to adhere them at both (top and bottom) surfaces of the specimen in such a way that they facilitate finding the bifurcation point caused by buckling by registering opposite trends in the measurement of strains resulting from the curvature of the specimen [45,75,76,78].…”
Section: Strain Monitoring and Controlling Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study into mechanical properties of carbon composites [8] revealed the dependence of articles quality on the processes for their obtaining; however, the issues related to the impact of a force scheme acting on a material during machining remained unsolved.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A dynamic mechanical analysis was used to characterize the storage modulus and loss factor. Xu et al investigate [14] the effects of complex state of stress on the compressive behaviour of 3D carbon/carbon composites by application of uniaxial and biaxial loadings using a specially developed Zwick cruciform testing facility. A semi-analytical method is proposed to determine the stress components in the gauge section of the biaxial specimen.…”
Section: Introductionmentioning
confidence: 99%